Developing Game Model for Migration Process of Static Timing Analysis Tools - Sargsyan, Tigran (Mathematical Problems of Computer Science, 2021)
The aim of the work is to find an adequate game model for Static Timing Analysis (STA) migration process and develop method for evaluating the efficiency of actions on each step of migration. For comparing timing models generated by STA tool an automated comparison utility was created which should be used for finding the best strategy in each cycle of migration process.